Violympic toán 9

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
nguyễn ngọc trang

Giải phương trình:

a)\(\dfrac{1}{3}\sqrt{x-2}-\dfrac{2}{3}\sqrt{9x-18}+6\sqrt{\dfrac{x-2}{81}}=4\)

b)\(\sqrt{x-2\sqrt{x-1}}=\sqrt{x-1}\)

Rimuru tempest
8 tháng 11 2018 lúc 19:01

a)ĐK \(x\ge2\)

\(\dfrac{1}{3}\sqrt{x-2}-\dfrac{2}{3}\sqrt{9\left(x-2\right)}+6\dfrac{\sqrt{x-2}}{\sqrt{81}}=4\)

\(\Leftrightarrow\dfrac{1}{3}\sqrt{x-2}-\dfrac{2}{3}.3\sqrt{x-2}+6\dfrac{\sqrt{x-2}}{9}=4\)

\(\Leftrightarrow\dfrac{1}{3}\sqrt{x-2}-2\sqrt{x-2}+\dfrac{2}{3}\sqrt{x-2}=4\)

\(\Leftrightarrow-\sqrt{x-2}=4\left(vl\right)\)

Rimuru tempest
8 tháng 11 2018 lúc 21:00

b) \(\sqrt{x-1-2\sqrt{x-1}+1}=\sqrt{x-1}\) (ĐK \(x\ge1\)

\(\Leftrightarrow\sqrt{\left(\sqrt{x-1}-1\right)^2}=\sqrt{x-1}\)

\(\Leftrightarrow\left|\sqrt{x-1}-1\right|=\sqrt{x-1}\)

\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x-1}-1=\sqrt{x-1}\\1-\sqrt{x-1}=\sqrt{x-1}\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}-1=0\left(vl\right)\\2\sqrt{x-1}=1\end{matrix}\right.\)

\(\Leftrightarrow\sqrt{x-1}=\dfrac{1}{2}\)

\(\Leftrightarrow x-1=\dfrac{1}{4}\)

\(\Leftrightarrow x=\dfrac{5}{4}\)


Các câu hỏi tương tự
Kim Trí Ngân
Xem chi tiết
ễnnguy Hùng
Xem chi tiết
Trúc Nguyễn
Xem chi tiết
Thánh cao su
Xem chi tiết
trần thị trâm anh
Xem chi tiết
Thánh cao su
Xem chi tiết
Ánh Nguyễn
Xem chi tiết
Mai Tiến Đỗ
Xem chi tiết
Nguyễn Mạnh Cường
Xem chi tiết